Exploring the Impact of Second-Child Mothers; Dislike on the Eldest Child:Understand its Influence and the Path to Building Intimate Relationships (Global Journal of Human-Social Science, 2024)
This study aims to explore the influence of the mother s dislike on the eldest child in the second-child family and to understand its influence and the way to establish intimate relationship By interviewing and analyzing the mothers and eldest children of five groups of second-child families the study found that the mother s dislike had a significant impact on the behavior and psychological state of the eldest children The results show that the mother s dislike will lead the eldest children to feel neglected and ignored thus affecting their study mood behavior and career choice In addition this study proposes to promote the establishment of intimate relationship between mother and eldest child through positive parent-child interaction emotional expression and support This study is of great significance to understand the influence of mother s dislike on the eldest child in the second child family and to establish a healthy parent-child relationship
Keywords: mother's dislike; eldest child; influence; intimate relationship; speech analysis; interview